2013
DOI: 10.1371/journal.pone.0058850
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Interactions between Successive Eye and Arm Movements: Signal Type Matters

Abstract: Spatial interactions between consecutive movements are often attributed to inhibition of return (IOR), a phenomenon in which responses to previously signalled locations are slower than responses to unsignalled locations. In two experiments using peripheral target signals offset by 0°, 90°, or 180°, we show that consecutive saccadic (Experiment 1) and reaching (Experiment 3) responses exhibit a monotonic pattern of reaction times consistent with the currently established spatial distribution of IOR. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…We found differences in the overall reaction times across the three conditions, with the shortest saccade latencies observed in the PT without placeholders condition and the longest latency observed in the central arrow condition. This difference in saccadic latency across conditions is reasonable as peripheral targets elicit more reflexive saccadic responses, responses that are likely to be faster than those elicited using central arrows (Abrams and Dobkin, 1994 ; Taylor and Klein, 2000 ; Fischer et al, 2003 ; Hilchey et al, 2012 ; Cowper-Smith et al, 2013 ). However, not only did we find differences in the overall reaction times across our three conditions, we also found differences in the patterns of effects of previous saccades on current saccade latency as a function of stimulus condition.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…We found differences in the overall reaction times across the three conditions, with the shortest saccade latencies observed in the PT without placeholders condition and the longest latency observed in the central arrow condition. This difference in saccadic latency across conditions is reasonable as peripheral targets elicit more reflexive saccadic responses, responses that are likely to be faster than those elicited using central arrows (Abrams and Dobkin, 1994 ; Taylor and Klein, 2000 ; Fischer et al, 2003 ; Hilchey et al, 2012 ; Cowper-Smith et al, 2013 ). However, not only did we find differences in the overall reaction times across our three conditions, we also found differences in the patterns of effects of previous saccades on current saccade latency as a function of stimulus condition.…”
Section: Discussionmentioning
confidence: 91%
“…For example, In the IOR literature, central arrows have been used to distinguish between effects that might arise from sensory vs. motor processes (Abrams and Dobkin, 1994 ; Taylor and Klein, 2000 ; Fischer et al, 2003 ; Hilchey et al, 2012 ; Cowper-Smith et al, 2013 ). It has been suggested that peripheral cues might elicit sensory effects due to repeated stimulation in the same retinal location and motor effects due to eye movement initiation, whereas central arrows are likely to elicit motor-related effects without the confound of repeated retinal stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IOR seems to be readily encoded in an object-based reference when manual responses are required (Tipper, Driver & Weaver, 1991;Tipper, Weaver, Jerreat, & Burak, 1994;Weaver, Lupianez & Watson, 1998;Tipper, Jordan & Weaver, 1999;Theeuwes, Mathot & Grainger, 2014;Smith, Ball, Swalwell & Schenk, 2016), but when saccadic responses are required, IOR may (Abrams & Dobkin, 1994;Tas, Dodd & Hollingworth, 2012;Swalwell, 2019) or may not (Abrams & Pratt, 2000;Senturk, Greenberg & Liu, 2016;Redden, Hilchey & Klein, 2018) be object-based. Contrary to Cowper- Smith et al (2013), Pratt and Neggers (2008) argue that separate inhibitory mechanisms influence pointing and oculomotor responses. Hunt and Kingstone (2003) asked their participants to make manual or saccadic localization responses to targets in alternate blocks while orthogonally manipulating target luminance and whether or not the fixation stimulus was removed at the time of the target.…”
Section: -A Phenomenon Without Consensus On Definition or Theoreticalmentioning
confidence: 83%